Pre – design survey of Ufa city squares using remote zoning data and GIS-technologies - Odintsov G. E.; Muftakhova S. I.; Ishbirdina L. M.; Garipova G. R.; Izimarieva Z. N. (E3S Web of Conferences)
The current state of four squares of the city of Ufa is studied in this paper. Comparative analysis of square area balance has shown that the paths and grounds areas for urban squares are significantly exceeded comparing to the normative values, at the same time the green plantations area is below the normative indicators in all studied squares. According to the aesthetic evaluation scale all the objects studied were assigned to class I except for Sh. Khudaiberdin Square. Species diversity among trees (from 5 to 9) and among bushes (from 2 to 7) was found. It has been established, that all squares trees and shrubs are in good condition. In order to identify the dynamics of the squares plantations condition, the analysis of the squares territory according to the NDVI index values on the satellite maps of Landsat for 2014 and 2022 was conducted. Some changes in the green planting structure of squares over the last 9 years have occurred. In the Lenin, Revolutionary Fighters and Mustai Karim Squares, the minimum and maximum, as well as average NDVI value index have increased, which indicates a significant improvement of green plantations over the studied period. In the Sh. Khudaiberdin Square, the minimum values decreased and the maximum, as well as average NDVI values index have also decreased, indicating a slight deterioration of green plantations condition and insufficient plant care.